An Integrative Review on the Feasibility and Acceptability of Delivering an Online Training and Mentoring Module to Volunteers Working in Community Organizations - Hill, Taylor G.; Langley, Jodi E.; Kervin, Emily K.; Pesut, Barbara; Duggleby, Wendy; Warner, Grace (Frontiers in Digital Health, 2021)
Background: Volunteer programs that support older persons can assist them in accessing healthcare in an efficient and effective manner. Community-based initiatives that train volunteers to support patients with advancing illness is an important advance for public health. As part of implementing an effective community-based volunteer-based program, volunteers need to be sufficiently trained. Online training could be an effective and safe way to provide education for volunteers in both initial training and/or continuing education throughout their involvement as a volunteer. Method: We conducted an integrative review that synthesized literature on online training programs for volunteers who support older adults. The review included both a search of existing research literature in six databases, and an online search of online training programs currently being delivered in Canada. The purpose of this review was to examine the feasibility and acceptability of community-based organizations adopting an online training format for their volunteers. Results: The database search identified 13,626 records, these went through abstract and full text screen resulting in a final 15 records. This was supplemented by 2 records identified from hand searching the references, for a total of 17 articles. In addition to identifying Volunteers Roles and Responsibilities; Elements of Training; and Evaluation of Feasibility and Acceptability; a thematic analysis of the 17 records identified the categories: 1) Feasibility Promoting Factors; 2) Barriers to Feasibility; 3) Acceptability Promoting Factors; and 4) Barriers to Acceptability. Six programs were also identified in the online search of online training programs. These programs informed our understanding of delivery of existing online volunteer training programs. Discussion: Findings suggested that feasibility and acceptability of online training were promoted by (a) topic relevant training for volunteers; (b) high engagement of volunteers to prevent attrition; (c) mentorship or leadership component. Challenges to online training included a high workload; time elapsed between training and its application; and client attitude toward volunteers. Future research on online volunteer training should consider how online delivery can be most effectively paced to support volunteers in completing training and the technical skills needed to complete the training and whether teaching these skills can be integrated into programs.